Productivity of incident management with conversational bots-a review - Orlando Iparraguirre-Villanueva; Luz Obregon-Palomino; Wilson Pujay-Iglesias; Fernando Sierra-LiÃ±an; Michael Cabanillas-Carbonell (IAES International Journal of Artificial Intelligence (IJ-AI), 2023)
The use of conversational agents (bots) in information systems managed by companyâ€™s increases productivity in the development of activities focused on processes such as customer service, healthcare, and presentation. The present work is a systematic literature review that collects articles from 2019 to 2022 in the databases Scopus, Springer, Willey, Indexes-Csic, Taylor & Francis, Pubmed, and Ebsco Host. PRISMA methodology was used to systematize 47 relevant articles. As a result of the analysis, 2/19 very important benefits were obtained, which are: helping to obtain information and facilitating customer service; as for the types of conversational bots, a total of 9 types were found, of which conversational agents and chatbots with artificial intelligence (AI) are the most common; in the case of processes, 3/5 processes that optimize conversational bots were found, where the most prominent are: teaching process, health processes, and customer service processes. An architecture model for conversational bots in incident management is also proposed.